Deletion of Glucose Transporter GLUT8 in Mice Increases Locomotor Activity - Schmidt, S. (Springer US, 2008)
Transport of glucose into neuronal cells is predominantly mediated by the glucose transporters GLUT1 and GLUT3. In addition, GLUT8 is expressed in some regions of the brain. By in situ hybridization we detected GLUT8-mRNA in hippocampus, thalamus, and cortex. However, its cellular and physiological function is still unknown. Thus, GLUT8 knockout (Slc2a8 (−/−)) mice were used for a screening approach in the modified hole board (mHB) behavioral test to analyze the role of GLUT8 in the central nervous system. Slc2a8 (−/−) mice showed increased mean velocity, total distance traveled and performed more turns in the mHB test. This hyperactivity of Slc2a8 (−/−) mice was confirmed by monitoring locomotor activity in the home cage and voluntary activity in a running wheel. In addition, Slc2a8 (−/−) mice showed increased arousal as indicated by elevated defecation, reduced latency to the first defecation and a tendency to altered grooming. Furthermore, the mHB test gave evidence that Slc2a8 (−/−) mice exhibit a reduced risk assessment because they performed less rearings in an unprotected area and showed significantly reduced latency to stretched body posture. Our data suggest that behavioral alterations of Slc2a8 (−/−) mice are due to dysfunctions in neuronal processes presumably as a consequence of defects in the glucose metabolism.